2020
DOI: 10.5588/pha.20.0053
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosed with TB in the era of COVID-19: patient perspectives in Zambia

Abstract: Introduction: Delayed TB diagnosis and treatment perpetuate the high burden of TB-related morbidity and mortality in resource-constrained settings. We explored the potential of COVID-19 to further compromise TB care engagement in Zambia.Methods: From April to May 2020, we purposefully selected 17 adults newly diagnosed with TB from three public health facilities in Lusaka, Zambia, for in-depth phone interviews. We conducted thematic analyses using a hybrid approach.Results: The majority of participants were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
0
22
1
1
Order By: Relevance
“…There is little information in the literature to explain these findings, so the reasons have to be speculative. A qualitative study in neighbouring Zambia found that patients recently diagnosed with TB during the COVID-19 pandemic were very concerned about contracting COVID-19 during clinic visits, perceiving the disease to be highly transmissible, deadly, and without effective treatment [27]. It is possible that these concerns were felt more keenly amongst mothers and their children, thus reducing the desire of the family unit to attend health facilities.…”
Section: Discussionmentioning
confidence: 99%
“…There is little information in the literature to explain these findings, so the reasons have to be speculative. A qualitative study in neighbouring Zambia found that patients recently diagnosed with TB during the COVID-19 pandemic were very concerned about contracting COVID-19 during clinic visits, perceiving the disease to be highly transmissible, deadly, and without effective treatment [27]. It is possible that these concerns were felt more keenly amongst mothers and their children, thus reducing the desire of the family unit to attend health facilities.…”
Section: Discussionmentioning
confidence: 99%
“…The use of aggregate quantitative data made it impossible to understand the cascade of care for TB case detection and HIV testing during COVID-19. Further mixed-methods research with both quantitative and qualitative analysis amongst TB patients themselves, as has been conducted in Zambia [ 38 ], are needed to obtain a better idea of why patient access to health services and health service delivery was so badly affected. We only assessed referrals of HIV-positive persons to ART and did not document the initiation or retention on ART.…”
Section: Discussionmentioning
confidence: 99%
“…15 When someone with a cough for more than 2-3 weeks comes to the MRC and is referred to a BTA sputum examination, they should receive education on how to collect purulent sputum, how to collect it in a pot. 1,16,17 Online communication using digital communication is a current solution that can be taken as a bridge between officers and sufferers. 18 This can be seen from the increase in respondents' knowledge and understanding after watching VisKomLAM 1 with a significance of 0.000 (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the current era of the Covid-19 pandemic, handling tuberculosis (TB) must remain a concern. 1,2,3 The World Health Organization (WHO) reports that Indonesia is in the third position with the highest cases of tuberculosis (TB) in the world. While the first and second positions are currently India and China.…”
Section: Introductionmentioning
confidence: 99%